STRUCTURAL ANALYSIS OF THE DRAMA SCRIPT "TEMANKU SAYANG TEMANKU MALANG (KEN KEMBALILAH SEPERTI DULU)" BY ELSA PEBRIYANTI - Siti Sopiah; Silmi Ahsanti Dewi; Elva Elfiani Salsa; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This article delves into the structural analysis of "Temanku Sayang Temanku Malang (Ken Kembalilah Seperti Dulu)", a drama script penned by Elsa Pebriyanti. The study aims to identify and examine the various structural elements that contribute to the overall narrative and thematic impact of the play. Through a critical analysis of the script, this research explores the ways in which Pebriyanti employs structural devices such as plot structure, character development, dialogue, and stage directions to convey the story's themes and messages. The analysis reveals that the script's narrative structure is characterized by a non-linear progression, with multiple flashbacks and flashforwards that blur the lines between past and present. This non-linear approach allows Pebriyanti to explore the complexities of human relationships and the consequences of past actions on the present. Furthermore, the study highlights the effective use of character development, particularly in the portrayal of the protagonist, whose emotional journey serves as a catalyst for the story's themes of love, loss, and redemption. The analysis also examines the role of dialogue in shaping the characters' personalities and relationships, as well as the ways in which stage directions contribute to the overall atmosphere and mood of the play. Additionally, the study discusses the significance of the play's title and its relationship to the themes and plot, highlighting the ways in which Pebriyanti uses the title to set the tone for the audience's engagement with the story. Ultimately, this research demonstrates that the structural elements of "Temanku Sayang Temanku Malang (Ken Kembalilah Seperti Dulu)" are carefully crafted to create a rich and nuanced narrative that explores the complexities of human relationships and the power of love and redemption. The study contributes to a deeper understanding of the script's structural dynamics and their impact on the audience's experience of the play.